Cyber Warfare And Its Place In Modern Geopolitics And War - Aryasatya, Idden; Daryanto, Eko (Security Intelligence Terrorism Journal (SITJ), 2025)
There are now major cybersecurity concerns as a result of how fast technology has changed geopolitics. Attacks against a nation's communication, infrastructure, and economy through cyber espionage, sabotage, disinformation, and DDoS attacks undermine national stability. The high level of digital integration in industrialized nations makes them easy targets, while the lack of resources and digital knowledge makes underdeveloped nations vulnerable. There has to be international collaboration on cybersecurity rules and ethics because of this chasm. While cutting-edge innovation like AI strengthens defenses, it also introduces new dangers and raises new ethical questions. This study delves into the consequences of cyberwarfare. It highlights the importance of strong cybersecurity measures, online education, and global cooperation to safeguard nations and their inhabitants against ever-changing cyber dangers.